1992
DOI: 10.1177/0013916592243004
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Chronic Stress Following a Natural Disaster and Discovery of a Human-Made Hazard

Abstract: Research on the acute and chronic effects of victimization by disaster has found that some patterns of response generalize across disasters of different origin and type. However, it is likely that variation in the nature of the victimizing event can affect long-term psychophysiological reactions. This study compared 23 flood victims with 27 people living near a leaking hazardous toxic waste dump and 27 control subjects. Self-report, behavioral, and physiological measures of stress were collected, all of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
9

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 15 publications
2
20
0
9
Order By: Relevance
“…D'autres auteurs, au contraire, rapportent l'existence de psychopathologies et de maladies sérieuses, répandues et persistantes conséquentes aux désastres (Adams & Adams, 1984;Erickson, 1976;Gleen, 1979;Gleser, Green, & Winget, 1981;Green et al, 1990;Lifton & Oison, 1976;Phifer & Norris, 3989;Rangell, 1976;Solomon & Davidson, 1997;Titchener & Kapp, 1976), La plupart des chercheurs ont toutefois constaté qu'au cours de la première année suivant l'exposition à une catastrophe, les individus vivent plusieurs situations difficiles (pertes financières, perte du domicile, conflits familiaux, apparition de problèmes de santé physique) qui perturbent généralement leur état de santé psychologique et physique (Norris et al, 2002). Les catastrophes peuvent également avoir des conséquences sur la réalisation des activités quotidiennes des victimes tant au niveau du travail, des loisirs, des activités de socialisation et des études étant donné l'importance des efforts qu'elles déploient pour se remettre des événements (Baum, Fleming, Israel, & O'Keefe, 1992;Canino, Bravo, Rubio-Stipec, & Woobury, 1990;Yates, 1992).…”
Section: Définitions Des Termes Sinistres Et Désastres Et Leur éTendueunclassified
“…D'autres auteurs, au contraire, rapportent l'existence de psychopathologies et de maladies sérieuses, répandues et persistantes conséquentes aux désastres (Adams & Adams, 1984;Erickson, 1976;Gleen, 1979;Gleser, Green, & Winget, 1981;Green et al, 1990;Lifton & Oison, 1976;Phifer & Norris, 3989;Rangell, 1976;Solomon & Davidson, 1997;Titchener & Kapp, 1976), La plupart des chercheurs ont toutefois constaté qu'au cours de la première année suivant l'exposition à une catastrophe, les individus vivent plusieurs situations difficiles (pertes financières, perte du domicile, conflits familiaux, apparition de problèmes de santé physique) qui perturbent généralement leur état de santé psychologique et physique (Norris et al, 2002). Les catastrophes peuvent également avoir des conséquences sur la réalisation des activités quotidiennes des victimes tant au niveau du travail, des loisirs, des activités de socialisation et des études étant donné l'importance des efforts qu'elles déploient pour se remettre des événements (Baum, Fleming, Israel, & O'Keefe, 1992;Canino, Bravo, Rubio-Stipec, & Woobury, 1990;Yates, 1992).…”
Section: Définitions Des Termes Sinistres Et Désastres Et Leur éTendueunclassified
“…An enormous number of laboratory experiments and field studies confirm the tight relationship between control and stress. For example, Baum and his associates have found that perceived loss of control is one of the most important mediators of reactions to disasters such as flooding, exposure to toxic waste, and the near meltdown of the Three Mile Island nuclear power plant (Baum, Cohen, & Hall, 1993;Baum, Fleming, Israel, & O'Keeffe, 1992).…”
Section: Control and Stressmentioning
confidence: 99%
“…Les échantillons de certaines études relatives à l'impact des désas-tres naturels sur le bien-être psychologique, sont principalement constitués par les victimes (Baum et al, 1992 ;Moore et Moore, 1994 ;Solomon et al, 1997). Lorsque ces échantillons concernent les intervenants, ceux-ci sont des secouristes lors de catastrophes traumatiques avec blessés et décès multiples (Bartone et al, 1989 ;Quarantelli, 1978 ;Stuhlmiller, 1994).…”
Section: Le Stress Associé Au Travail Lors De Désastres Naturelsunclassified